Creative tourism as a zone of entrepreneurship and innovation in management - Yulia L. Rybakova; Olga V. Karpova; Igor L. Kaverzin (Управление культурой)
The article presents the results of a theoretical and practical study on the state and potential for the development of creative tourism in the Russian Federation. The authors traced the change in approaches to the concept of creative tourism in the process of the development of the tourism and hospitality industry from a separate area of the service sector to a complex interregional ecosystem. It is important to emphasize that the key feature of the current stage of development is the view of the tourism sector - as well as the sphere of cultural and creative industries - in the optics of the ecosystem, emphasizing the importance of the systemic connectivity of all its elements, the relationship with many related industries and areas of the local economy. The authors not only analyzed the semantic and functional approaches to the developing direction of creative tourism, but also studied the influence of the formation of the local entrepreneurship market as one of the significant drivers of the formation of the product basis of creative tourism. The article formulates criteria for assessing the effectiveness, efficiency and potential of projects in the field of creative tourism, and discusses a number of cases reflecting the specific features of the implementation of the creative tourism concept in Russia (Kolomenskaya Pastila, Kolomna; New Tourist Geography, New Culture of Souvenirs, St. Petersburg; Museum Retreat, Yaroslavl Region; With Intent on Crafts, Nizhny Novgorod Region; Arkhstoyanie and Nikola-Lenivets, Kaluga Region; Demidov Park, Sverdlovsk Region; Crystal City Dyatkovo, Bryansk Region; All-Russian Youth Educational Marathon «Tourproject»). An important factor in the formation and development of the competence potential of creative tourism should be considered the systematic development of human capital; this article discusses the main challenges in this field, including the growth in the cost of human capital in the industry. The criteria - attributes are formulated, based on which a project can be classified as creative tourism. Conclusions: the growing interest in domestic tourism in Russia creates a new competitive field, new demands that can only be met through entrepreneurship, but with government support; the development of creative tourism requires the formation of a support policy, where it is important to determine the subjects, priorities and mechanisms; the expansion of the concept and approach to creative tourism is recorded, a methodological toolkit for inclusion in the field of creative industries is in demand; human development in the industry is required; the sphere needs product development, both offline and online.